Mexican immigrant health advantage in metabolic syndrome? Examining the contributions of demographic, socioeconomic, and health behavior characteristics - Maria Carabello; Julia A. Wolfson (Elsevier, 2021)
Although Mexican immigrants to the United States (US) have historically held health and mortality advantages over US-born groups, evolving population dynamics in Mexico paired with shifts in Mexico-US immigration patterns and policy regimes have raised new concerns about the metabolic health of recent cohorts of Mexican immigrants. Using a nationally representative sample of adults aged 20-years and older (n = 10,833) from the National Health and Nutrition Examination Study (NHANES, 1999-2016), we assess and seek to explain differences in metabolic syndrome (MetS) risk by race-ethnicity, country of origin, and duration of residence in the US and evaluate whether recent Mexican immigrants continue to exhibit a metabolic health advantage. We decompose the difference in MetS prevalence between US-born whites (45.5%) and recent Mexican immigrants (29.5%) to determine how demographic, socioeconomic, and health behavior characteristics contribute to the patterning of metabolic health. Findings reveal that recent Mexican immigrants hold a metabolic health advantage over all groups, which is accounted for by their younger age structure. Yet recent Mexican immigrants would retain a sizable age-adjusted MetS advantage if they were to achieve parity with US-born whites on education, income, and food security. To ensure that newly-arrived Mexican immigrants continue to experience historically favorable health and mortality prospects, modest policy changes could offer health-promoting protections in the form of increased economic and food security, as well as improved educational opportunities for younger immigrants.